(3/2)h+1=2h+5

Simple and best practice solution for (3/2)h+1=2h+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3/2)h+1=2h+5 equation:



(3/2)h+1=2h+5
We move all terms to the left:
(3/2)h+1-(2h+5)=0
Domain of the equation: 2)h!=0
h!=0/1
h!=0
h∈R
We add all the numbers together, and all the variables
(+3/2)h-(2h+5)+1=0
We multiply parentheses
3h^2-(2h+5)+1=0
We get rid of parentheses
3h^2-2h-5+1=0
We add all the numbers together, and all the variables
3h^2-2h-4=0
a = 3; b = -2; c = -4;
Δ = b2-4ac
Δ = -22-4·3·(-4)
Δ = 52
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$h_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$h_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{52}=\sqrt{4*13}=\sqrt{4}*\sqrt{13}=2\sqrt{13}$
$h_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-2)-2\sqrt{13}}{2*3}=\frac{2-2\sqrt{13}}{6} $
$h_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-2)+2\sqrt{13}}{2*3}=\frac{2+2\sqrt{13}}{6} $

See similar equations:

| 3(8+n)-15=-2n+9+5n | | k/12+0=30 | | (25+15+18+p)*4=20 | | 9-b+5b=2b-7 | | 3/5x+7=16 | | 2(2g+1)=5g | | 8+7b=134 | | 1-2r+3r=-1 | | 3x+24=-3x-18 | | 4a-3=6+6a-8+5 | | 0.16(2x+1)=0.8x+0.32 | | -4n+2=30 | | 2y+6+3y=2(2y-6)+7 | | y/6+11=-15-3y | | 3f-1=2f+8 | | 4=z-73/5 | | 3+7=-5(5x-2) | | -7-6(5n-2)=-85 | | -15=-5/6x | | x−12=−65 | | -x/3+10=12 | | 4n+30=30 | | 15=0.5+2x+10 | | -2x(x-3)=12 | | 4(2m-5)-3m=20m+5m | | 2m-3/5-m/3=-6/5 | | 6x-4+10x-18=15x-13 | | a+4.8=9.2 | | 4,5y=16.65 | | -14k=6k=8 | | (12-2u=9u+45 | | {25+15+18+p}{4}=20 |

Equations solver categories